Revolutionizing the fight against antimicrobial resistance with artificial intelligence - Kusuma, Ikhwan Yuda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
Antimicrobial resistance (AMR) is a major public health threat, responsible for millions of deaths annually. Current efforts to combat AMR include antibiotic stewardship programs, infection prevention and control measures, and the development of new antimicrobial agents. However, traditional laboratory techniques used to identify antibiotic-resistant genes are inadequate. Artificial intelligence (AI) has emerged as a promising tool to combat AMR, potentially facilitating rapid diagnosis, predicting antibiotic resistance patterns, and identifying new treatments. AI can analyze large amounts of data from various sources and identify patterns and correlations that humans may miss. However, there are potential challenges and risks associated with implementing AI in the fight against AMR, including ethical concerns and data quality issues.